Dramaturgi Dakwah Hanan Attaki Pada Komunitas Geng Motor di Bandung - Cholil; Nur Syam; Yasyva Agfa Nizar (Jurnal Komunikasi Islam, 2021)
This paper discusses how Hanan Attaki’s da’wah innovation in Bandung in the perspective of dramaturgy theory. Research questions are answered using a literature study, with a historical and sociological analysis approach to Hanan Attaki’s da’wah innovations through the work of other researchers and related sources. The results of the study show that Hanan Attaki has succeeded in embracing the motorcycle gang community in Bandung which has been synonymous with brawls and fights by taking several approaches, including through conveying messages in a contemporary style that is easily accepted by young people and through the involvement of young people in making da’wah activities on social media., such as Instagram, Twitter and Youtube.